Regional policy after renewed lisbon strategy and implications for Turkey: A comparison between east and west - Yeşiltepe, Burçin (My University, 2010)
The global leadership in this new millennium does not only require having an efficient foreign policy or major military power, but it also requires being innovative and economic power. In this context, the Lisbon Strategy, launched to make the EU the most competitive and dynamic knowledge based economy by 2010, was an important roadmap for the global leadership, which is the next step for the Union after deeper and wider integration. Despite its successful objectives in identifying future challenges of the Union, the Lisbon Strategy has failed in its first implementation period due to the administrative, economic and social disparities among the member states. Those disparities indeed would be an obstacle for the Union on its path to global leadership. Accordingly, first the Lisbon Strategy re-launched in 2005 and then the regional policy of the Union, which aims to reduce economic and social disparities within the Union and prevent the future ones, went under a major reform in 2006. In that sense 2006 reform, in line with Lisbon objectives, introduced successful mechanisms to the policy domain. Amongst the other mechanisms, the Instrument for Pre-accession Assistance is the most important one for Turkey as a candidate country since it aims to support the efforts to come closer to European standards and policies. However when the regional disparities and different regional development approaches in Turkey taken into consideration, the Instrument for Pre-Accession Assistance would not be enough to reduce such disparities and differences. In that context, a weak Europeanization process may lead to a Turkey, whose membership would weaken the future dynamism of the Union.

Yeni binyılda küresel liderlik sadece etkin bir dış politika ya da büyük askeri güç ile mümkün olmamakta aynı zamanda yenilikçi ve ekonomik bir güç olmayı gerektirmektedir. Bu bağlamda, Avrupa Birliği’ni 2010 yılına kadar dünyanın en rekabetçi ve dinamik ekonomisine dönüştürmeyi amaçlayan Lizbon Stratejisi, Birlik’in daha derin ve geniş entegrasyon sürecinin bir sonraki aşaması olan küresel liderlik arayışında önemli bir yol haritası olmuştur. Ancak hedefleriyle gelecek dönemdeki zorlukları iyi tahlil eden Lizbon Stratejisi, çoğunlukla üye ülkeler arasındaki idari, ekonomik ve sosyal kapasite farklılıklar nedeniyle, ilk beş yıllık sürede amaçlarına ulaşamamıştır. Bu farklılıklar uzun vadede Birlik’in küresel liderlik hedefine de sekte vurabileceği için önce 2005 yılında Lizbon Stratejisi gözden geçirilerek yeniden sunulmuş ve hemen ardından da 2006 yılında, birlik içindeki mevcut farklılıkları azaltmayı ve gelecekte oluşabilecek farklılıkları önlemeyi amaçlayan Bölgesel politika, stratejinin hedefleriyle uyumlu olarak yenilenmiştir. 2006 Reformu genel amaçları bağlamında bölgesel politikaya başarılı yenilikler getirmiştir. Bu yenilikler arasında önemli bir yer tutan ve aday ülkelerin Avrupa standartları ve politikalarıyla uyum çabalarını destekleyen Katılım Öncesi Mali Yardım Aracı, aday bir ülke olan Türkiye açısından en önemli mekanizmayı oluşturmaktadır. Bununla beraber bu araçla sağlanan destekler, Türkiye’nin kendi içindeki ciddi bölgesel farklılıklar ve bunları aşmak için kullandığı bölgesel kalkınma yaklaşımlarının Avrupa Birliği’nden farklılığı göz önüne alındığında yeterli olmayacaktır. Bu bağlamda zayıf ilerleyen bir Avrupalılaşma süreci ise üyelik durumunda Avrupa Birliği’nin gelecekteki dinamizmini zayıflatan bir Türkiye’ye neden olabilecektir.
Keywords: Avrupa Birliği; Türkiye_Uluslararası İlişkiler; Uluslararası İlişkiler